Nurses' Perceptions of Caring Behavior at St. Elizabeth Hospital, Medan 2023 - Irene Pernanda Naibaho; Mestiana Br. Karo; Lili Suryani Tumanggor (Jurnal EduHealth, 2026)
Caring is a moral attitude in nursing practice, the caring nature of nurses when dealing with sick people and patient families. Every day must show that nurses really care about the situation. Caring behavior is an action based on caring, compassion, skills, empathy, responsibility, sensitivity, and support. In general, caring behavior is a form of basic nursing practice in which the patient feels comfortable and assisted in carrying out the patient's healing process more quickly. The purpose of this study is to determine nurses understanding of caring behavior This research uses a qualitative approach with the phenomenological method. The data collection is carried out by means of in-depth interviews with 5 questions to dig deeper into the understanding of nurses in caring behavior. Taking participants using simple random sampling technique 5 participants. The data analysis technique used is thematic analysis. Based on the results of direct interviews, the results obtain: Caring is a sense of good interpersonal relationships, being sensitive and concerned about the patient's condition. Caring behavior is when providing nursing care to patients. Caring behavior can be given by showing empathy and sincerity towards patients, trying to overcome patient complaints and not discriminating between patients. Caring behavior is very beneficial for patients so that they feel satisfied and happy with their treatment, build a trusting relationship and improve the quality of nursing care. There are obstacles in the implementation of caring behavior, namely when nurse cares and serves the patient well, but the patient refuses and gets angry.